Attack : with a National 'Clean Throat' campaign / by A, Corbett-Smith - Corbett-Smith, Arthur, 1879-
1929-10 1929 1920s 9 pages The 'common cold' implies (a) lowered bodily vitality and (b) an infective throat, mouth and nasal cavities. Given those conditions and the enemy is within the gates. The germs of pneumonia, diphtheria, influenza, tuberculosis may become active from an otherwise healthy body. CAUSES OF DISEASE Thus, as Sir George Newman remarks, "it is obvious that serious disease and even death may result (a) indirectly, from dental caries, oral sepsis, inflammation of the nose, sore throat and similar conditions ; (b) directly, from persons coughing or speaking to other persons or even breathing in their faces." "People," he adds, "must be taught that diphtheria germs do not live in drains, but in throats, and are readily conveyed to others." The world-wide influenza epidemic of 1918-19 destroyed uncounted millions. In the great towns of England alone the death rate during the last quarter of 1918 was 11 per 1000 of the population. Early in 1929 we met another outbreak, the most severe since 1918. For the first quarter of the year the death rate in our great towns was nearly 3 per 1000. The first quarter of 1930 is at hand! PREVENTABLE And all this is preventable! Disease is an abnormal condition. It need not exist. There is no more reason why we should develop the 'common cold' or pneumonia or influenza or tuberculosis than that we should have small-pox or syphilis. A hundred years or so ago small-pox was endemic. It was regarded as a perfectly natural, if unhappy, state of man. To-day, "small-pox is the perquisite of those who prefer to have it." Now mark the official pronouncement of the Ministry of Health upon those respiratory diseases and their allies :— A CLEAN MOUTH AND CLEAR RESPIRATORY PASSAGES, with a complete abstinence from spitting and sneezing, cough-spraying or breathing at other people, WOULD GO A LONG WAY TOWARDS THE COMPLETE PREVENTION OF THE FIVE DISEASES NAMED." EDUCATE THE INDIVIDUAL In short, the solution of the problem lies in the effective education of the individual. And that is precisely the solution of well-nigh every problem before the world to-day, from Disarmament and Empire Settlement to the preservation of the English countryside. The immediate future of Medicine lies not in cure but in prevention. 2 200/B/3/2/C693/3/13